Elucidating the Biological Role of Neuronal Dystonin Isoforms in the Hereditary Sensory Neuropathy Dystonia Musculorum - Ferrier, Andrew R. (Université d'Ottawa / University of Ottawa, 2013)
Dystonin is a cytoskeletal linker protein whose loss-of-function in dystonia musculorum (dt) mice results in a hereditary sensory neuropathy with profound sensory ataxia. The dystonin gene (Dst) is exceptionally large (~400 kb) producing three giant neuronal dystonin isoforms (>600 kDa) through alternative splicing, namely dystonin-a1, -a2, and -a3. Although loss of expression of dystonin-a1 and -a2 is sufficient to cause dt pathogenesis, the causal dystonin-a variant and the pathological mechanisms activated upon their individual loss remains unclear. Moreover, while the primary pathology lies in the sensory neurons of dt mice, the overt movement disorder coupled with dystonin’s expression in motor neurons, suggests the motor system may also be affected. Here we report that dt mice exhibit motor neuron defects, including, but not limited to, aberrant phosphorylation of neurofilaments, axonal swellings, reduced axon branching and immature neuromuscular junctions. Furthermore, we find that various pathologies (e.g., Ca2+ dyshomeostasis, unfolded protein response (UPR) induction, caspase activation, and apoptosis) within dt sensory neurons are attributable to the specific loss of dystonin-a2. Coupled with this, transgenic mice exogenously expressing dystonin-a2 within the nervous system of dt mice attenuated the degeneration of sensory neuron subtypes, and was sufficient to ameliorate the phenotype and increase life span. Despite these improvements, however, both dystonin-a2 and dystonin-a1 appear necessary for complete amelioration of dt pathogenesis. Finally, pertubations in autophagic activity underlie the degeneration of dt sensory neurons. Restoring dystonin-a2 expression in dt sensory neurons rescues this autophagic defect. Taken together, our work reveals that dystonin-a loss-of-function imparts defects on the neuromuscular system that likely contribute to the dt phenotype. Moreover, although loss of dystonin-a2 expression impedes key biological processes, such as autophagy, endoplasmic reticulum (ER) dynamics and intracellular trafficking, and elicits numerous pathological mechanisms, this work suggests the dt disorder to be a multi-isoform disease.